If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(u + -6) = 8u + -24 Reorder the terms: 6(-6 + u) = 8u + -24 (-6 * 6 + u * 6) = 8u + -24 (-36 + 6u) = 8u + -24 Reorder the terms: -36 + 6u = -24 + 8u Solving -36 + 6u = -24 + 8u Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '-8u' to each side of the equation. -36 + 6u + -8u = -24 + 8u + -8u Combine like terms: 6u + -8u = -2u -36 + -2u = -24 + 8u + -8u Combine like terms: 8u + -8u = 0 -36 + -2u = -24 + 0 -36 + -2u = -24 Add '36' to each side of the equation. -36 + 36 + -2u = -24 + 36 Combine like terms: -36 + 36 = 0 0 + -2u = -24 + 36 -2u = -24 + 36 Combine like terms: -24 + 36 = 12 -2u = 12 Divide each side by '-2'. u = -6 Simplifying u = -6
| 7(x-6)-3=-4(-7x+9)-3x | | c=(77-32)*(5/9) | | 71=-2n+23 | | 5x+1=5x+x | | c=(77-32)*5/9 | | 8+3-11=-9 | | -3n+13=40 | | x-4+3x+100=180 | | 7x+3=97.32 | | -2x+9-5x= | | (3x+3)(4x+6)= | | 7(x-y)-3=-4(-7x+9)-3x | | 6=30-8N | | 8+3-11=9 | | 8+3-11= | | -n+13=99 | | 10-4x=3x | | 3a*4c= | | 30x^3-150x^2+210x-50=0 | | 6+2q=10+7 | | x*20=15 | | 20+4+8x= | | 9x+7=10x+14 | | 17x-7=9x+x | | 9x+7=910x+14 | | 8p+24=11p+33 | | -6x+8(x+3)=8 | | F(9)=7x+8 | | 2(b+4)=4(0.5b+3) | | -17=-3v+7(v-7) | | 5(2x+3)=-3(2x+1) | | 80=37.98+0.25x |